RANCANG BANGUN ALAT TENUN BUKAN MESIN (ATBM) DENGAN PENGENDALI PLC SEBAGAI ALAT TENUN MEKATRONIKA - Wartiono, Totok; -, Wiyono; Nusantara, AEB. (Universitas Muhammadiyah Semarang, 2015)
Design of handloom with PLC controllers aims to optimize the process of manufacture woven fabrics in small industry in the district. Sukoharjo. The main problems experienced by users is the length of time handloom woven fabric production as a result of the movement still manually using hands and feet. PLC function replaces lade movements, stamping, and rolling the fabric using a piston. Air from the high pressure compressor reduced pressure once the water vapor content of the regulator. PLC programmable valve connected to direct air into each cylinder active. The program structure adapted to the construction of woven fabric. Handloom operation simply by pressing a button that is not required excessive time and energy. The design of equipment include: PLC Amron 20 AC, pneumatic cylinders; Single valve 24; Speed control; Red Switch DC 24 V and 3 pushbutton switches; 6mm hose;Naple; Regulators; Compressor 1PK; Handloom and thread. Results Design of handloom with the addition of PLC controllers generate 40 meters per day of production before the design is 20 meters per day with one operator, so there was an increase of 50 percent from the prior design and build. The advantage is flexible, the change and error correction easy, visual observation, speed of operation, safety, the addition a series of quick, simple control system components, reprogramming fast, high efficiency, the amount of production increases as woven fabric qualityisbetter.Keywords: handloom, thread, PLC, Pneumatic Cylinder, Compressor.